PERAN DAN PENGARUH KOMPETENSI DAN PROFESIONALISME AUDITOR INTERNAL TERHADAP KUALITAS AUDIT - Nukman Aziz (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to comprehensively analyze the role and influence of the competence and professionalism of internal auditors on audit quality. In this context, competence includes the knowledge, skills and attitudes of internal auditors in carrying out audit tasks. Meanwhile, professionalism includes work ethics, independence, objectivity, and the auditor's professional responsibility in presenting honest and fair audit results. To achieve the research objectives, the research method used in this article is a comprehensive literature analysis and mapping of the latest empirical studies that are relevant to the topic. Data obtained from various sources will be analyzed critically to present a clear picture of how the competence and professionalism of the internal auditors impact the resulting audit quality. The results of the study conclude that adequate competence will increase the effectiveness of the auditor in carrying out audit tasks, while professionalism will ensure objective and fair audit results. These two factors play an important role in ensuring that internal audit provides significant added value to the organization and stakeholders. Therefore, developing the competence and professionalism of internal auditors must be a priority in efforts to improve audit quality and achieve organizational goals in a sustainable manner.